Under what conditions is brood reduction effective?. Issue 4 (3rd July 2020) - Lee, Jong K.; Chung, Ok-Sik
Abstract : Hatching asynchrony in birds occurs when incubation commences prior to clutch completion and results in broods containing different aged and sized nestlings. The brood reduction hypothesis predicts that hatching asynchrony is a strategy that facilitates the partial success of brood, as feeding to old and large nestlings which results in adaptive brood reduction under periods of food shortage. Using stochastic simulation, we tested and specified the outcome of the brood reduction hypothesis with various provisioning variables of birds to investigate under what conditions the brood reduction effectively explains the evolution of hatching asynchrony. Asynchronous hatching can be productive as provisioning by parents is preferentially feeding to old nestlings when food is not sufficiently available, while it did not create substantial differences in the number of nestlings fledged when food was equally allocated to all nestlings. Secondly, in the case where food items are large and fewer deliveries are needed, asynchronous hatching becomes more favoured compared to smaller, more frequently delivered, food items. Also, when parents provision less food than was needed on bad days, hatching asynchrony became favoured even when the bad days occur infrequently. Different life traits of each bird can change the expectation of the brood reduction hypothesis.